2010
DOI: 10.1136/hrt.2009.183822
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of functional mitral regurgitation to new-onset atrial fibrillation in acute myocardial infarction

Abstract: There is a graded independent association between the severity of FMR and the new onset of AF in patients with AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 31 publications
2
36
1
2
Order By: Relevance
“…It has recently been demonstrated that a moderate mitral regurgitation after an acute myocardial infarction affects the degree of ventricular remodelling through different molecular and cellular mechanisms 15. This suggests that FMR is not simply a bystander but has a direct effect on excess remodelling, enhanced risk of atrial fibrillation16 and subsequent clinical events 17…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been demonstrated that a moderate mitral regurgitation after an acute myocardial infarction affects the degree of ventricular remodelling through different molecular and cellular mechanisms 15. This suggests that FMR is not simply a bystander but has a direct effect on excess remodelling, enhanced risk of atrial fibrillation16 and subsequent clinical events 17…”
Section: Discussionmentioning
confidence: 99%
“…Mitral regurgitation has a well-recognized association with AF, 78 and more severe mitral regurgitation has been shown to predict progression from paroxysmal AF to permanent AF, 79 incident AF after myocardial infarction, 80 and AF recurrence after PV isolation. 81 A study by Maeillo et al 82 noted that LA enlargement in the setting of mitral regurgitation tends to be more spherical than that occurring with diastolic dysfunction, which tends to be more eccentric, suggesting that the more spherical modeling is more relevant to the development of AF.…”
Section: Clinical Studies Of Af and Diastolic Dysfunctionmentioning
confidence: 99%
“…Reports on whether the left ventricular (LV) infarction localization is a risk factor for MR severity differ: the incidence of ischemic MR has been reported to be higher in inferior compared to anterior MI localization [1,6,15]; however, the difference in incidence of moderate or severe MR based on MI localization was reported as insignificant by other author teams [3,12].…”
Section: Discussionmentioning
confidence: 94%
“…It is reasonable to expect some overlap between these two clinical entities, however incidence and prevalence of significant MR is much higher in MI population or patients with prior MI, indicating important role of myocardial ischemia and LV remodeling [5,6]. Important role of LV remodeling is further supported by identifiable predictors of ischemic MR, confirmed and consistent with minor variations throughout the published studies and our results: extent of CAD, previous MI, larger LV dimensions and volumes, and decreased LV systolic function [2,3,11,12,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation